Penambahan Probiotik Herbal dengan Dosis yang Berbeda terhadap Respon Stres Benih Ikan Gabus - Ardini, Astri; Parirska, Donny; Lestari, Siti (Jurnal Ilmiah Pertanian dan Peternakan, 2024)
Purpose: This study aims to determine the stress response of snakehead fish (Channa striata) fry when herbal probiotics are incorporated into their feed. The use of herbal probiotics is intended to enhance fish health and resilience in aquaculture systems, especially during stressful conditions. Method: The research employed an experimental method using a Completely Randomized Design (CRD) with specific probiotic dosage treatments. The probiotic used was herbal-based and applied at a concentration of 10 ml/kg of feed. Results: The results indicated a positive effect on stress response indicators. The operculum opening rate was recorded at 57 times per minute, survival rate reached 71.11%, and feed efficiency achieved 74.24%. Additionally, water quality parameters such as temperature (26–29°C) and pH (6–8) remained within optimal ranges throughout the study, supporting the effectiveness of probiotic treatment. These findings suggest that herbal probiotics at 10 ml/kg dosage positively influence physiological and environmental adaptation in snakehead fry. Conclusion: The administration of herbal probiotics in feed at 10 ml/kg improves stress tolerance, survival, and feed efficiency of snakehead fry. It provides a natural solution to reduce physiological stress and enhance performance in aquaculture practices. Limitations: The study was limited to a single dosage (10 ml/kg) and conducted under controlled laboratory conditions, which may differ from field scenarios. Contribution: This study supports the use of herbal probiotics as functional feed additives that stimulate appetite, enhance immune response, reduce stress, and support hematological health in snakehead fish cultivation.